Disruption of Stat3 reveals a critical role in both the initiation and the promotion stages of epithelial carcinogenesis - Chan, Keith Syson (American Society for Clinical Investigation, 2004)
Constitutive activation of signal transducer and activator of transcription 3 (Stat3) has been found in a wide spectrum of human malignancies. Here, we have assessed the effect of Stat3 deficiency on skin tumor development using the 2-stage chemical carcinogenesis model. The epidermis of Stat3-deficient mice showed a significantly reduced proliferative response following treatment with the tumor promoter 12-O-tetradecanoylphorbol-13-acetate (TPA) because of a defect in G1-to-S-phase cell cycle progression. Treatment with the tumor initiator 7,12-dimethylbenz[a]anthracene (DMBA) resulted in a significant increase in the number of keratinocyte stem cells undergoing apoptosis in the bulge region of hair follicles of Stat3-deficient mice compared with nontransgenic littermates. Notably, Stat3-deficient mice were completely resistant to skin tumor development when DMBA was used as the initiator and TPA as the promoter. Abrogation of Stat3 function using a decoy oligonucleotide inhibited the growth of initiated keratinocytes possessing an activated Ha-ras gene, both in vitro and in vivo. In addition, injection of Stat3 decoy into skin tumors inhibited their growth. To our knowledge, these data provide the first evidence that Stat3 is required for de novo epithelial carcinogenesis, through maintaining the survival of DNA-damaged stem cells and through mediating and maintaining the proliferation necessary for clonal expansion of initiated cells during tumor promotion. Collectively, these data suggest that, in addition to its emerging role as a target for cancer therapy, Stat3 may also be a target for cancer prevention strategies.